Pediatric Trigger Thumb: Congenital or Developmental? A Unique Case Report - Venkatadass, Krishnamoorthy; Bhardwaj, Praveen; Sabapathy, S. Raja (Journal of Hand and Microsurgery, 2020)
Pediatric trigger thumb is the new terminology for the so-called congenital trigger thumb. This change in appellation was suggested based on recent knowledge acquired through prospective studies of a large number of newborns for the presence of trigger thumb at birth across many centers. In this background, we came across a newborn with trigger thumb which was diagnosed right after birth, putting aside all theories of nonexistence of congenital trigger thumb. We report a case of congenital trigger thumb diagnosed at birth, which was managed surgically at 9 months of age, who has good clinical and functional outcomes at 1-year follow-up. Herewith, we would like to submit that congenital trigger thumb does exist, though might be a very rare occurrence.
Keywords: congenital; pediatric; trigger; thumb